On Inextensible Flows Of Tangent Developable of Biharmonic B-Slant Helices according to Bishop Frames in the Special 3-Dimensional Kenmotsu Manifold - Asil, Vedat; Korpinar, Talat; Turhan, Essin (Soc Paranaense Matematica, 2013)
In this paper, we study inextensible flows of tangent developable surfaces of biharmonic B - slant helices in the special three-dimensional Kenmotsu manifold K with eta-parallel ricci tensor. We express some interesting relations about inextensible flows of this surfaces.
Keywords: Biharmonic curve; Developable surface; Kenmotsu manifold; Bishop frame